Water control by employing microgrooves inside gas channel for performance improvement in polymer electrolyte fuel cells. (6th July 2015) - Koresawa, Ryo; Utaka, Yoshio
Abstract Further performance improvement in polymer electrolyte fuel cell (PEFC) and their popularization face several problems even though they have been commercialized. The water behavior in PEFCs is closely related to cell performance. To enhance the cell performance, it is necessary to effectively remove the generated water. In this study, to improve the water control in gas channels, a novel gas channel with microgrooves, which are fabricated inside the channel walls, is applied. The generated water is removed through the microgrooves to facing side of the gas channel by capillary and shear forces from air flow. The performance of the PEFC with and without microgrooves was examined in various experimental conditions: cell temperature, relative humidity of gas, and air velocity. It was shown that the PEFC with microgrooves showed better performance than conventional PEFC without microgrooves. In particular, value of current density increased by approximately 16% when the air velocity was 8.0 m/s.